ZINTEGROWANIE POLSKICH KONCEPCJI WYKŁADNI PRAWA - Zieliński, Maciej; Bogucki, Olgierd; Choduń, Agnieszka; Czepita, Stanisław; Kanarek, Beata; Municzewski, Andrzej (Wydział Prawa i Administracji UAM, 2009)
The authors present an extremely important thesis. They claim that Polish conceptions of interpretation of law (and there are nine o f them) have led to the development of a certain ‘common good’ in Polish legal culture. This ‘common good’ consists, on the one hand, of those elements of the nine conceptions (or their methodological foundations) which are common, e.g. an assumption that the subject of interpretation is a legal text, or an assumption that a legal text has a normative character, and those other elements of those conceptions which have been sufficiently justified either in science or in the attitudes of legal interpreters, and subsequently reviewed in judicial decisions (e.g. three types of interpretation and the order in which they are applied).
INTEGRATION OF POLISH CONCEPTIONS OF INTERPRETATION OF LAW